2013
DOI: 10.1007/s00213-013-3057-1
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic hallucinogens differentially modify gamma and high frequency oscillations in the rat nucleus accumbens

Abstract: RationaleThe nucleus accumbens (NAc) is a site critical for the actions of many drugs of abuse. Psychoactive compounds, such as N-methyl-d-aspartate receptor (NMDAR) antagonists, modify gamma (40-90) and high frequency oscillations (HFO, 130–180 Hz) in local field potentials (LFPs) recorded in the NAc. Lysergic acid diethylamide (LSD) and 2,5-dimethoxy-4-iodoamphetamine (DOI) are serotonergic hallucinogens and activation of 5HT2A receptors likely underlies their hallucinogenic effects. Whether these compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 46 publications
4
30
0
Order By: Relevance
“…Initial reports of vStr oscillations in behaving rats suggested that low-gamma (~50 Hz) and high-gamma (~80 Hz) power were differentially modulated upon approach to and receipt of reward (Berke, 2009;van der Meer & Redish, 2009;Howe et al, 2011). The relationship between aspects of reward processing and vStr gamma power is further substantiated by the apparent influence of dopaminergic and cannabinoid drugs on vStr gamma power (Berke, 2009;Morra et al, 2012;Goda et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Initial reports of vStr oscillations in behaving rats suggested that low-gamma (~50 Hz) and high-gamma (~80 Hz) power were differentially modulated upon approach to and receipt of reward (Berke, 2009;van der Meer & Redish, 2009;Howe et al, 2011). The relationship between aspects of reward processing and vStr gamma power is further substantiated by the apparent influence of dopaminergic and cannabinoid drugs on vStr gamma power (Berke, 2009;Morra et al, 2012;Goda et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, the impact of serotonergic hallucinogens on neuronal oscillations, and particularly the association of these oscillations with identifiable conscious states, is unclear. Initial animal studies performed with the hallucinogenic serotonin (5-HT) 2A/2C agonist, 1-[2,5-dimethoxy-4-iodophenyl]-2-aminopropane (DOI), reported a DOI-induced reduction in delta (0.3-4 Hz) and gamma (30-80 Hz) oscillations in the prefrontal areas of the brain (Celada et al 2008;Puig et al 2010), in addition to a trend toward an increase in higher frequency (70-90 Hz) oscillations in subcortical structures (Goda et al 2013). In humans, oscillations decreased across a broad frequency range (up to 20 Hz) during eyes closed resting state after the administration of ayahuasca, a plant brew containing N,N-dimethyltryptamine (DMT), another naturally occurring serotonergic hallucinogen (Riba et al 2002;Riba et al 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Key to this multilevel analysis are temporal structures in the brain, including brain rhythms [2, 24]. Rhythmic alterations occur in schizophrenia and its animal models, accompany all neurotransmitter system manipulations that produce psychotic-like behavior [5, 2529], and are candidate endophenotypes of the disease [30]. Rhythms are believed to play a key role in coordinating the activity of neuronal populations across multiple spatial and temporal scales [3134], and are known to be associated with a wide range of cognitive and perceptual processes [35, 36].…”
Section: Introductionmentioning
confidence: 99%